Translation, History and Arts : New Horizons in Asian Interdisciplinary Humanities Research. - Ji, Meng (Professor of translation studies) (Cambridge Scholars Publishing, 2013)
Translation, History and Arts: New Horizons in Asian Interdisciplinary Humanities Research is a collection of selected research papers originally presented at the Todai Forum in October 2011 in Lyon, France, under the auspices of the University of Tokyo, Japan. Papers selected for inclusion in this book stand at the frontier of interdisciplinary humanities research, and are concerned with translation and cross-cultural studies, social and art history, and comparative area studies. A central t ...